2018
DOI: 10.1002/jlb.2a1117-449r
|View full text |Cite
|
Sign up to set email alerts
|

IRAK4 activity controls immune responses to intracellular bacteria Listeria monocytogenes and Mycobacterium smegmatis

Abstract: IL-1 receptor-associated kinase (IRAK) 4 is a central enzyme of the TLR pathways. This study tested the hypothesis that IRAK4 kinase activity is prerequisite for regulating innate immunity during infections with intracellular bacteria. To this end, we analyzed responses of macrophages obtained from mice expressing wild-type (WT) IRAK4 or its kinase-inactive K213M mutant (IRAK4 ) upon infection with intracellular bacteria Listeria monocytogenes or Mycobacterium smegmatis. In contrast to robust induction of cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The identified five quinones in this study seem to be more selective to IRAK1, whereas IRAK1/4 dual inhibitors hit both IRAK1 and IRAK4 enzymes. Usually, IRAK1/4 dual inhibitors possess two different biological activities, which could be an advantage of the IRAK dual inhibitor by maximizing the pharmacological efficacy, but when the defect is only in IRAK1 kinase and a selective targeting is required, that could provoke unwanted side effects and increased toxicity because direct inhibition of IRAK4 and other IRAK4-dependent downstream signaling cascades could lead to dysregulation of critical physiological functions in humans, such as the removal of developing autoreactive B cells and the induction of innate immune responses against bacterial and viral infections. , Therefore, selectively targeting IRAK1 with high efficacy and low side toxicity may provide an alternative safer approach of targeting IRAK1-mediated inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…The identified five quinones in this study seem to be more selective to IRAK1, whereas IRAK1/4 dual inhibitors hit both IRAK1 and IRAK4 enzymes. Usually, IRAK1/4 dual inhibitors possess two different biological activities, which could be an advantage of the IRAK dual inhibitor by maximizing the pharmacological efficacy, but when the defect is only in IRAK1 kinase and a selective targeting is required, that could provoke unwanted side effects and increased toxicity because direct inhibition of IRAK4 and other IRAK4-dependent downstream signaling cascades could lead to dysregulation of critical physiological functions in humans, such as the removal of developing autoreactive B cells and the induction of innate immune responses against bacterial and viral infections. , Therefore, selectively targeting IRAK1 with high efficacy and low side toxicity may provide an alternative safer approach of targeting IRAK1-mediated inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…JNK is a wellknown signaling molecule playing a crucial role in cellular stress conditions, and when activated, phosphorylated JNK can also alter the mitochondria to increase its ROS production significantly, creating a positive feedback loop (44). Mice expressing inactive mutant form of IRAK4 were found to be more susceptible to Listeria monocytogenes and Mycobacterium smegmatis systemic infections due to impaired induction of inducible nitric oxide synthase (iNOS) mRNA (45). Since TBK1 was also involved in mitophagic regulation of mitochondrial physiology and expression of iNOS mRNA during inflammatory assault, paired with the reduction of ROS production, we hypothesized that the inhibitory characteristics of sulfatide may come from the upper hierarchy (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…25 In the MyD88-dependent pathway, the recruitment and formation of MyD88-IRAK4-IRAK1 complex (also called Myddosome) leaded to IRAK1 phosphorylation and its dissociation from the complex, free IRAK1 activated cascades of downstream kinases and contributed to the activation of NF-κB. [26][27][28] Previous studies showed that macrophages harboring kinaseinactive IRAK4 exhibited deficient activation of IRAK1, MAPKs and NF-κB, and reduced expression of TNF-α, IL-6, IL-1β after bacterial infections, 29 which suggested that the expression of NF-κB and downstream pro-inflammatory cytokines were affected by IRAKs. In this study, expression of IRAK4 and NF-κB were found in the breeding period and pre-hibernation, which suggested TLR4/MyD88 signaling could induce the next reaction by activation of IRAK4.…”
Section: Discussionmentioning
confidence: 99%